STUDY OF STATISTICAL CORELATION AMONG FISH PRODUCTION AND INDIAN OCEAN DIPOLE AND MONSOON IN WESTERN INDONESIAN SEA USING SATELLITE DATA - SUPRATMAN -; I Wayan Arthana (Master Program of Environmental Science, Postgraduate Program of Udayana University)
Western Indonesian Sea especially Sumatra Sea, Sunda Strait, Pelabuhan Ratu Sea and Prigi Sea is a potential areafor fisheries especially tongkol. Oceanography factors that influenced to the fisheries activity are Sea SurfaceTemperature (SST), Sea Surface Height (SSH), concentration chlorophyll-a (Chl-a), monsoon and Indian Ocean Dipole.This research location is in Western Indonesian Sea. With coordinate is 97.00 E to 114.00 E, and 02.00 N to 11.00 Sin period of 2002 to 2006. Spatial and temporal analysis SSH from Jason-1 Satellite, SST and chl-a from AQUA-MODISsatellite data set used to correlation with fish production. The correlation between Dipole Mode Index (DMI) and fishproduction is use also. SST and chl-a data processing by SeaDAS software, SSH derive from website NASA, DMIderived from website NASDA. Fish production data is from statistic fish production data.The correlation value between fish production and SST in Sumatra Sea and Pelabuhanratu Sea is high with value -0.734 and -0.660. In Sunda Strait and Prigi Sea is low, with value -0.560 and -0.566. Meanwhile the correlation valuebetween fish production and chl-a in Sumatra Sea, Sunda Strait and Pelabuhanratu are high and in Prigi Sea is low. Thevalue in Sumatra Sea is 0.868, in Sunda Strait is 0.660, in Pelabuharatu Sea is 0.751 and in Prigi sea is 0.588.The fish production caught by fisherman influence by northwest monsoon (rainy season) and southeast monsoon (dryseason). Fish production will decrease in rainy season, and increase at dry season.The correlation value between fish production and DMI has a high correlation in Sumatra Sea, Sunda Strait andPelabuhanratu Sea. Meanwhile, in Prigi Sea the corelation is low. Correlation value in Sumatra Sea is 0.851, in SundaStrait is 0.656, in Pelabuhanratu Sea is 0.691 and in Prigi Sea is 0.463.